Bancada didática para sistema de refrigeração por absorção - Queiroz, Márcio Henrique Bastos de (2013)
This paper presents the development and construction of a bench didactic system for domestic absorption. The goal is to help in the training process and students' learning of UTFPR and cooling professionals, by demonstrating the operation as an illustration the operation of the refrigeration cycle. For the development and construction of the bench was necessary to purchase a Junior Ice Consul, and materials and components for manufacturing the same. The bench was grown on a tubular metal casters to facilitate movement and the reuse of components used. The work will contribute to the training of future technologists and engineers in understanding the physical phenomena involved in the absorption refrigeration system, giving it knowledge to work in the field of refrigeration and maintenance service.